Image-based 3D canopy reconstruction to determine potential productivity in complex multi-species crop systems - Burgess, Alexandra J.; Retkute, Renata; Pound, Michael P.; Mayes, Sean; Murchie, Erik H. (Oxford Journals, 2017)
Background and Aims: Intercropping systems contain two or more species simultaneously in close proximity. Due to contrasting features of the component crops, quantification of the light environment and photosynthetic productivity is extremely difficult. However it is an essential component of productivity. Here, a low-tech but high resolution method is presented that can be applied to single and multi-species cropping systems, to facilitate characterisation of the light environment. Different row layouts of an intercrop consisting of Bambara groundnut (Vigna subterranea (L.) Verdc.) and Proso millet (Panicum miliaceum) have been used as an example and the new opportunities presented by this approach have been analysed.